The role of chatbots in paediatric chronic disease management: Trends, findings, and future recommendations - Amelia Arnis; Yeni Rustina; Allenidekania Allenidekania; Fariz Darari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Chronic diseases in children, such as chronic kidney disease (CKD), diabetes, and asthma require complex long-term management because they can affect the quality of life physically, psychologically, socially, and educationally. One of the new innovations in supporting the management of chronic diseases in children is the use of chatbots that play a role in education, health monitoring, and psychological support. Purpose: To review the literature on the effectiveness of chatbots in supporting self-care in children with chronic diseases. Method: This literature review study examined the effectiveness of chatbots in supporting self-care in children with chronic diseases. The articles used were from ProQuest, Scopus, ScienceDirect, and Google Scholar. Inclusion criteria included publications from 2014-2024 that focused on children with chronic diseases. The search keywords used were